Teaching ROI Analysis in an Era of Social Media. (November 2014) - Cronin, John J.
Measuring the financial performance of communication programs is essential, and ROI (return on investment) is the most important measure of financial performance. But university programs in advertising and marketing communication often have given little attention to ROI. The result has been complaints from business executives that graduates of these programs are inadequately prepared to conduct a financial analysis of communication campaigns. The calculation of ROI for social media campaigns is more complex than might be thought and adds to the challenge facing students. This paper describes the difficulties of performing financial analysis of social media campaigns and suggests a six-step process for teaching this important topic.